MAKSIMISASI PENDAPATAN ABON IKAN PADA CV. DUTA AGRO LESTARI DI KOTA PALU SULAWESI TENGAH - Rusniati S.Politon; Sahari Kassa; Effendy Effendy (Universitas Tadulako, 2018)
This research aimed was to determine the amount of fish floss and resources used in order to maximize profit at fish floss business of Duta Agro Lestari CV. It was conducted at Duta Agro Lestari CV with consideration that this CV is a well-known fish floss enterprise with the highest production capacity in Palu. The research was done from September – October 2015. Respondents were determined purposively consisting of one leader and five employees in the Duta Agro Lestari. The analysis results of Programming Linear showed that for each fish floss package of 100 g, 150 g, 200 g and 250 g, they are optimally sold at 95, 75, 75, and 80 units, respectively. In order to increase the CV profit, the resources used should be 100 kg of raw material, 132 person-days of labor force, IDR 414,000 spent for gas and IDR 224,000 spent for oil.